Estimation of the stapes-bone thickness in the stapedotomy surgical procedure using a machine-learning technique. - Kaburlasos, V.G (IEEE Transactions on information technology in biomedicine)
Stapedotomy is a surgical procedure aimed at the treatment of hearing impairment due to otosclerosis. The treatment consists of drilling a hole through the stapes bone in the inner ear in order to insert a prosthesis. Safety precautions require knowledge of the nonmeasurable stapes thickness. The technical goal has been the design of high-level controls for an intelligent mechatronics drilling tool in order to enable the estimation of stapes thickness from measurable drilling data. The goal has been met by learning a map between drilling features, hence no model of the physical system has been necessary. Learning has been achieved as explained in this paper by a scheme, namely the d-σ Fuzzy Lattice Neurocomputing (dσ-FLN) scheme for classification, within the framework of fuzzy lattices. The successful application of the dσ-FLN scheme is demonstrated in estimating the thickness of a stapes bone "on-line" using drilling data obtained experimentally in the laboratory.